Enhancing behavioural intention among young consumers to choose green hotels evidence from a frontier market - Achchuthan, S.; Prahalathan, B.; Umanakenan, R.; Kajenthiran, K. (University of Jaffna, 2021)
Despite the increasing popularity of green hotels, there is a dearth of research and literature on consumer attitudes toward green hotels. The purpose of this study is to investigate consumer intention to visit a green hotel in Sri Lanka by examining the effect of biospheric and egoistic values on consumer attitudes toward green hotels and desire for green hotels. An online survey was distributed among young consumers through google forms by using social media neworks (Facebook and LinkedIn). Three-hundred and twenty-six (326) consumers were eligible to participate in the survey and 280 respondents were used for the further analysis. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to analyse the collected data, assess the model and test hypotheses. The findings indicate that biospheric value is a highly significant predictor of consumer attitudes and desires toward green hotels. Additionally, it appears that the desire for green hotels is a stronger predictor of green hotel visit intention than the attitude toward green hotels. This is the first study to deepen our understanding of the two psychological theories namely goal-directed behaviour and value-belief-norm theory in the context of green hotel. To this end, the findings of the study provide unique cues for managers and green hotel practitioners in developing marketing strategies to enhance behavioural intention among young consumers to choose green hotels.
Keywords: Biospheric value; Consumer attitude; Consumer desire; Egoistic value; Green hotel visit intention